Navigating the nuances of studying animal facial behaviors with Facial Action Coding Systems - Florkiewicz, Brittany N. (Frontiers in Ethology, 2025)
Facial Action Coding Systems (FACS) are some of the most systematic and standardized methods for studying the physical aspects of animal facial behavior. Although FACS manuals provide some guidance on how to implement their coding system, they often lack detailed recommendations for data collection protocols, which impacts the types of data that can be coded. Furthermore, there are various methods for data coding that are not always discussed in FACS. In this perspective piece, I aim to review some considerations related to the data collection and coding process and to offer best practice recommendations, as well as alternatives. While this list of considerations and recommendations is not comprehensive, I hope it encourages more discussions and the sharing of additional guidelines and protocols for FACS. By doing this, we can enhance the systematic approach and scientific rigor of FACS further.